The Influence of Celebrity Endorsement on Purchase Decisions through Brand Awareness and Brand Image as mediation Yamaha Nmax Motorcycle Users in Yogyakarta - Marsandhi, Alvito Marsandhi; Setiawan, Budi; Azwar, Azwar (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study examines the influence of celebrity endorsement on purchase decisions with brand awareness and brand image serving as mediating variables among Yamaha NMAX users in Yogyakarta. The research is conducted in response to intense competition within the motorcycle industry and fluctuating sales trends, highlighting the need for effective marketing strategies to influence consumer purchasing behavior. A quantitative research design was applied using a survey method, with questionnaires distributed to 200 respondents selected through purposive sampling. Data analysis was carried out using Structural Equation Modeling (SEM) based on the Partial Least Square (PLS) approach. The findings reveal that celebrity endorsement has a positive and significant impact on brand awareness and brand image. Furthermore, brand image significantly influences purchase decisions, whereas brand awareness does not exhibit a significant effect on purchase decisions. In addition, celebrity endorsement does not directly affect purchase decisions in a significant manner. These results suggest that the impact of celebrity endorsement on purchase decisions is primarily mediated through brand image rather than through direct influence or brand awareness. The study emphasizes the importance of leveraging celebrity endorsement to strengthen brand image in order to enhance consumer purchase decisions.